Preparing effective illustrations. Part 2: photographs, images and diagrams - Ng, K.H.; Peh, W.C. (Stamford Publishing Pte Ltd / Singapore Medical Association, 2009)
In part two of "Preparing effective illustrations", the other three categories, viz. photographs, radiological images and diagrams, are discussed. Illustrations provide visual information to supplement the results in a scientific paper, and create a visual impact that can improve the readability of a paper. This article provides some basic guidelines to assist authors in preparing effective photographs, radiological images and diagrams.